A phylogeny for the Drosophila montium species group: a model clade for comparative analyses - Conner, William R. (Mol Phylogenet Evol, 2020)
The Drosophila montium species group is a clade of 94 named species closely related to the model species D. melanogaster. The montium species group is distributed over a broad geographic range throughout Asia, Africa, and Australasia. Species of this group possess a wide range of morphologies, mating behaviors, and endosymbiont associations, making this clade useful for comparative analyses. We use genomic data from 42 available species to estimate the phylogeny and relative divergence times within the montium species group, and its relative divergence time from D. melanogaster. To assess the robustness of our phylogenetic inferences, we use 3 non-overlapping sets of 20 single-copy coding sequences and analyze all 60 genes with both Bayesian and maximum likelihood methods. Our analyses support monophyly of the group. Apart from the uncertain placement of a single species, D. baimaii, our analyses also support the monophyly of all seven subgroups proposed within the montium group. Our phylograms and relative chronograms provide a highly resolved species tree, with discordance restricted to estimates of relatively short branches deep in the tree. In contrast, age estimates for the montium crown group, relative to its divergence from D. melanogaster, depend critically on prior assumptions concerning variation in rates of molecular evolution across branches, and hence have not been reliably determined. We discuss methodological issues that limit phylogenetic resolution – even when complete genome sequences are available – as well as the utility of the current phylogeny for understanding the evolutionary and biogeographic history of this clade.